2011
DOI: 10.7763/ijbbb.2011.v1.11
|View full text |Cite
|
Sign up to set email alerts
|

Micronucleus Test in Exfoliated Buccal Cells from Chromium Exposed Tannery Workers

Abstract: Abstract-Our aim was to investigate the adverse effects of occupational exposure to trivalent chromium in tannery workers and unexposed persons. Trivalent chromium used in tanning industry is an environmental contaminant that acts as a carcinogen towards humans and animals. The carcinogenic potential of metals is a major issue in defining human health risk from exposure. In the present investigation, 84 tannery workers and 52 control subjects with similar mean ages, smoking prevalences and alcohol consumption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 25 publications
4
13
0
Order By: Relevance
“…The result obtained from the present study corroborates with the findings of a preliminary study conducted on automobile spray painters in the coal camp mechanic village in Enugu [23]. More so, previous studies have documented similar increased levels of MN and other nuclear abnormalities in buccal epithelial cells of workers occupationally exposed to potentially genotoxic substances [9,[24][25][26].…”
Section: Onyemelukwe Et Alsupporting
confidence: 91%
See 1 more Smart Citation
“…The result obtained from the present study corroborates with the findings of a preliminary study conducted on automobile spray painters in the coal camp mechanic village in Enugu [23]. More so, previous studies have documented similar increased levels of MN and other nuclear abnormalities in buccal epithelial cells of workers occupationally exposed to potentially genotoxic substances [9,[24][25][26].…”
Section: Onyemelukwe Et Alsupporting
confidence: 91%
“…Furthermore, there was a significantly higher MN frequency in the buccal cells of car spray painters who were older than 35 years when compared to those <35 years. This finding suggests that there may be an association between an individual's age and the frequency of MN, as previously documented [26]. In line with this finding, a previous study also reported a significant change in MN frequency due to age in a study involving automobile painters in South India [27].…”
Section: Onyemelukwe Et Alsupporting
confidence: 84%
“…Further micronucleus frequency was also increased in buccal cells in Chromium Exposed Tannery Workers and silicaexposed workers [15,16].…”
Section: Discussionmentioning
confidence: 81%
“…The shell part of A. scoparia was soaked in phosphoric acid 2% for 24 hours and then dried at 80 ºC in an oven for 24 hours [6,7,[25][26][27][28][29]. Dry parts were then ground and passed through standard steel sieves (72 mm mesh size).…”
Section: Experimental Design and Chemical Analysismentioning
confidence: 99%
“…Hexavalent chromium is considered the most hazardous of all forms, and in welding fume it is a suspected human carcinogen. DNA damage in welders has been associated with hexavalent chromium exposure 7 . This is consistent with the classification of hexavalent chromium as a human lung carcinogen 8 .…”
mentioning
confidence: 99%